Implementation of the Independent Curriculum: Educational Innovation that Encourages Learning Independence - Wahyuni, Annisa; M. Hasbi; Kanada, Rabial (International Journal of Applied Educational Research (IJAER), 2024)
This study aims to analyze the implementation of the Independent Curriculum in Madrasah Aliyah Negeri 2 Palembang using a qualitative descriptive approach. This research involves subject teachers, madrasah heads, curriculum waka, and students as key and supporting informants. Data collection was carried out using semi-structured interview techniques, non-participatory observation, and documentation. The data obtained was analyzed through four stages: data reduction, data display, data verification, and drawing conclusions to describe the implementation of the curriculum in depth. The results of research related to the implementation of the Independent Curriculum at Madrasah Aliyah Negeri 2 Palembang show a significant impact on students' academic and social performance. Academically, curriculum flexibility allows students to choose topics and learning methods according to their interests, leading to improved academic understanding and skills. Project-based and research-based learning methods develop critical thinking and problem-solving skills, as evidenced by better academic outcomes and increased achievement. On the social side, the curriculum strengthens collaboration and communication skills between students through group projects and community activities. This increases students' sense of community and confidence, as well as their participation in extracurricular activities. However, challenges such as unequal access to resources and limited teacher training need to be addressed. With adequate support and periodic evaluation, the positive impact of the Independent Curriculum is expected to be maximized, encouraging the holistic development of students at Madrasah Aliyah Negeri 2 Palembang.